Human macrophages release exosomes containing anti-inflammatory microRNAs after phagocytosis of Leishmania infantum - Hudachek, Cinthia L.; Zhanbolat, Bayan; Chen, Yani; Wilson, Mary E. (Frontiers in Immunology, 2025)
IntroductionThe protozoan Leishmania infantum causes visceral leishmaniasis, a disease associated with suppressed systemic innate and adaptive immune responses. Mechanisms underlying the generalized immune suppression are incompletely understood. Exosomes are a subset of microvesicles released from eukaryotic cells, which contain proteins, lipids, and nucleic acids, including microRNAs (miRNAs). These small regulatory RNAs can simultaneously modify the expression of many genes and pathways. We hypothesized that L. infantum infection of macrophages induces the release of exosomes containing immunomodulatory miRNAs that contribute to systemic immunosuppression during visceral leishmaniasis.MethodsUsing NanoString arrays, we profiled exosomal miRNAs released by infected versus uninfected human macrophages. Differential expression was validated by RT-qPCR, and functional effects were tested by transfecting miR-mimics.ResultsSeveral miRNAs were augmented in infected exosomes, including hsa-miR-223-3p which has anti-inflammatory activities. Previous studies showed that the NLRP3 inflammasome pathway might be targeted by differentially expressed miRNAs, a hypothesis that was confirmed in transfected THP-1 monocytic cells overexpressing hsa-miR-223-3p.DiscussionWe show that L. infantum infection induces the release of exosomes containing miRNAs that are capable of modifying the host immune environment, possibly suppressing microbicidal pathways and favoring parasite survival.